Effects of medicinal plants, Alisma canaliculatum, Laminaria japonica and Cornus officinalis, treated with probiotics on growth performance, meat composition and internal organ development of broiler chicken - Sarker, Md Sazedul Karim; Kim, Gwi Man; Sharmin, Farhana; Yang, Chul Ju (Asian Journal of Medical and Biological Research, 2017)
A trial was conducted with 175 day old Ross broiler chicks to evaluate the effectiveness of Alisma canaliculatum (Water plantain or Theksa), Laminaria japonica (Sea tangle or Dashima) and Cornus officinalis (Cornelain cherry or Sansuyu) medicinal plants treated with probiotics in replacing antibiotic. Three medicinal plants were prepared in dry and flour form with treatment of probiotics. The groups were control (basal diet), antibiotic (basal diet + 0.05% OTC, oxytetracycline), Water plantain treated with Probiotics (WPP) 0.5%, Sea tangle treated with Probiotics (STP) 0.5% and Cornelian cherry treated with Probiotics (CCP) 0.5% in basal diet. The broilers were distributed in a completely randomized design having 5 replications with 7 chicks per replication in wire cage. The data were analyzed by SAS package program. Addition of three medicinal plants in broiler diets didnt show negative effect on growth and feed conversion efficiency in broilers. Significantly highest protein percentage in broiler meat was found in groups fed the three medicinal plants treated with probiotics (WPP, STP and CCP) compared with other groups (P<0.05). Crude ash also increased significantly by the three medicinal plants addition compared to control especially in breast meat (P<0.05). Addition of probiotics treated with medicinal plants had similar beneficial effects on most of the observed parameters to those found in antibiotic-fed groups, so it implies that these three medicinal plants can be the possible alternatives to antibiotic for broiler production. Asian J. Med. Biol. Res. December 2016, 2(4): 696-702